Making Deservingness of the Unemployed Conditional: Changes in Public Support for the Conditionality of Unemployment Benefits - Buß, C; Ebbinghaus, B; Naumann, E (Edward Elgar Publishing, 2017)
Since the 1990s, stricter conditions for the (long‐term) unemployed to receive benefits have been on the ‘activation’ agenda. However, policymakers are constrained in their reform efforts by the economic and fiscal situation, the pre‐existing institutional contexts and public opinion. This cross‐national and longitudinal study investigates whether the social legitimacy of benefit obligations for the unemployed is affected by the changing economic situation and the varying institutional context. We use data from the European Values Survey, a repeated cross‐sectional survey that was conducted in 1990, 1999 and 2008 in 23 European countries. Support for the conditionality of unemployment benefits is measured with an item that asks whether people who are unemployed should have to take any job available. We find that the main economic indicators – economic growth and the unemployment rate – are significantly related to support for conditionality. People living in wealthier countries are more likely to be in favour of conditionality, whereas a high unemployment rate reduces such support. With regard to institutional features, we find some support for the assumption that people in welfare states with more generous social policies prefer stricter conditionality for access, in order to protect the generous benefits against any misuse.